A review on the association of SNP at rs731236 of VDR Gene and different diseases in various ethnicity - Rafique, Usrat Rifat Binte (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.